E-Procurement in Malaysian construction industry: benefits and challenges in implementation - Mohd Nawi, Mohd Nasrun; Deraman, Rafikullah; Bamgbade, Jibril Adewale; Zulhumadi, Faisal; Mehdi Riazi, Salman Riazi (ExcelingTech Publishers, 2017)
In this paper, the benefits and challenges embedded in Electronic procurement (e-procurement or e-Perolehan) are highlighted. Specifically, the benefits of introducing e-procurement for tendering and online registration of businesses and companies in Malaysia was emphasized. The study highlighted E-procurement advantages such as cost reduction, improved efficiency in government business with the aid of internet-based information and communication technology. The study concluded with recommendations to policy makers to pay more attention to the availability of infrastructure such as information technology for a better E-procurement implementation.